Fetal CNS Damage with Maternal Prenatal Trauma - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
The neurologic findings in nine infants who were exposed to maternal trauma during pregnancy are reported from the University Hospital Essen, Hufelandstr, Germany.